Primary Non-Hodgkin's Lymphoma Mimicking Lateral Epicondylitis - Aktürk, Semra; Çetintaş, Derya; Gucer, Tulin Kaya; Kaya, Arzu (My University, 2016)
Primary bone lymphoma constitutes 3-7% of all malign bone tumors and extra-nodal lymphomas. Joint infiltration is very rare clinical entity and mono arthritis may be a secondary synovial reaction to adjacent bone disease or direct synovial involvement. Radiological features of primary lymphoma of bone may present with different findings. Lateral epicondylitis is one of the most causes of elbow pain. It is usually observed between 30 and 50 years of age. The main symptom is the pain at the lateral epicondyle of the elbow. We report a case of primary Non-Hodgkin's Lymphoma mimicking lateral epicondylitis a 61 years female patient. It emphasizes the need for a high clinical suspicion in susceptible cases, particularly in permanent bone and joint pain
Keywords: Genel ve Dahili Tıp; Onkoloji